LRFD bridge design specifications. (American Association of State Highway and Transportation Officials, 2020)
The AASHTO LRFD Bridge Design Specifications are intended for use in the design, evaluation, and rehabilitation of bridges. The specifications employ the Load and Resistance Factor Design (LRFD) methodology, using factors developed from current statistical knowledge of loads and structural performance. This new 9th edition includes revisions to almost all sections of the specifications.
"Pub code: LRFDBDS-9."
Keywords: Bridges -- Design and construction -- Specifications -- United States.; Bridges -- Live loads -- Specifications -- United States.; Bridges -- Maintenance and repair -- Specifications -- United States.; Bridges -- Earthquake effects.; Earthquake resistant design.; Structural analysis (Engineering) -- Handbooks, manuals, etc.; Earthquake hazard analysis.; Strains and stresses.; Elastic analysis (Engineering); Load factor design.; Soil-structure interaction.; Soil mechanics.; Shear strength of soils.; elektronické knihy; electronic books